The Role of Sensory Marketing in Ice Cream Parlor Purchase Decisions - Castillo Placencia, Fabián Andrés; Lindao Narváez, Heidy Yajaira; Feijoo Jaramillo, Irene Maria; Sarmiento Chugcho, Carlos Bolívar (Revista Universidad de Guayaquil, 2025)
In today’s competitive and dynamic environment, ice cream parlors face the challenge of staying relevant in the face of new trends, market evolution and changes in consumer tastes and preferences. Traditional marketing strategies are losing effectiveness and becoming obsolete. According to Kotler, Kartajaya, and Setiawan (2017), marketing innovation is crucial to adapt to changing customer needs. Furthermore, Pine and Gilmore (2019) highlight the importance of creating meaningful experiences for users, which is vital to maintaining competitiveness. Recent studies by Smith and Colgate (2018), Lemon and Verhoef (2016), Wirtz and Lovelock (2016), and Kumar and Reinartz (2018) reinforce the need to update marketing strategies to meet current consumer expectations. This research adopts a quantitative, correlational and non-experimental design based on cross-sectional data. Data collection was carried out through a self-administered questionnaire in Google Forms. The reliability of the instrument was measured using Cronbach’s alpha coefficient. Data analysis was carried out using SmartPLS 4.00, a tool commonly used in sensory marketing studies. The sample consisted of 283 participants, predominantly young people between 18 and 25 years old. The descriptive statistical results indicated significant positive correlations between visual, olfactory and gustatory factors and their impact on purchase decisions. The regression analysis revealed that the visual (β = 0.456, p < 0.001) and gustatory (β = 0.321, p < 0.002) factors significantly and positively influence price perception. However, sensory (β = 0.06, p = 0.284) and olfactory (β = -0.051, p = 0.378) factors did not show a significant relationship with price perception. These findings are consistent with the literature that identifies visual and gustatory stimuli as key determinants in the perception of product value (Iglesias, Guillén, & Peña, 2021; Garay Tuanama, 2021). The results indicate that visual and gustatory factors have a significant and positive influence on price perception, while sensory and olfactory factors do not show a significant relationship. This aligns with existing literature suggesting that visual and gustatory stimuli are crucial in forming product value perceptions. Despite evidence suggesting that olfactory stimuli can affect consumer behavior (Chirinos Retuerto, 2020), this study did not find a significant relationship with price perception. Future studies should further explore these relationships, considering potential moderating variables and different contexts. This study highlights the importance of integrating sensory marketing strategies in ice cream shops. By improving the sensory environment, ice cream parlors can significantly improve the customer experience and increase their competitiveness in a rapidly changing market. The findings provide valuable insights for managers looking to leverage sensory marketing to foster customer loyalty and satisfaction, thereby driving sales and brand differentiation in a saturated market.